ANALISIS KONSEP PENDIDIKAN RUMAH TANGGA DALAM ISLAM MENURUT PERSPEKTIF DR. AISYAH DAHLAN - Mumu; Elis Lisna Khoerunnisa (Program Studi Pendidikan Agama Islam, 2024)
The concept of household education in Islam has various views, one of which is the perspective of Dr. Aisyah Dahlan who emphasizes the household as a place of rest and creates a peaceful atmosphere. Nevertheless, many couples start a household with a minimum of knowledge, especially in terms of religion. Every aspect of life in Islam has rules aimed at seeking prosperity and becoming a field of charity. It is not easy to build a wholesome household; the husband and wife must have sufficient knowledge of the right values, norms, and morals and mental readiness to face challenges. Many couples feel ready but fail to the goal of building a happy and prosperous household. This study examines in depth Dr. Aisyah Dahlan's thinking about household education in Islam, using library research methods and content analysis techniques. (content analysis). Some of the main principles in the concept of household education according to Dr. Aisyah Dahlan include: the importance of communication, an authoritative pattern of caring based, emotional and spiritual health, and Islamic religious education. A holistic approach that combines emotional, psychological, and spiritual aspects has proven effective in creating harmonious and happy families, enhancing family relationships, conflict management, and happiness